Low MYH9 expression predicts a good prognosis for hepatocellular carcinoma - Lin, Xian (Int J Clin Exp Pathol, 2018)
Hepatocellular carcinoma (HCC) is currently one of the most common causes of cancer-related death and one of the most commonly diagnosed cancers. MYH9 is thought to play a critical role in cancer progression. However, the expression and prognostic value of MYH9 in HCC are still unknown. In this study, the expression and biological significance of MYH9 were evaluated in HCC, at mRNA and protein levels. We showed that both mRNA and protein levels of MYH9 were significantly upregulated in HCC relative to the levels in adjacent non-tumor tissues based on the TCGA database and immunohistochemical analysis, respectively (P < 0.001). Additionally, we found that high MYH9 protein levels correlated with poor patient prognosis (median survival 19 months versus 49 months) (Log-Rank, P = 0.0292). Meanwhile, our data suggested that MYH9 expression is an independent prognostic factor for HCC after surgical resection (HR = 0.675, 95% CI 0.452-1.008, P = 0.054) and can potentially serve as a biomarker for the clinical diagnosis and prognosis of HCC.